DEBATES ON HALAL ISSUES AS INDONESIAN CONTEMPORARY RELIGIOUS SOCIAL PHENOMENA - Dzukroni, Arisy Abror; Ulinnuha, Roma (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
The government obligates halal certification for all products across Indonesia to capture the larger halal market. In 2025, Indonesia's total consumption of goods and services will reach US$ 330.0 billion. Modernity that requires society to increase economic and religious feasibility is a good combination for capitalists. This modernity has subsequently transformed into a halal lifestyle and has penetrated various sectors of the life of the modern Muslim community. However, Foucault says that power is a determining factor for the discourse that develops in society. The qualitative methods and unstructured observation completed with library data as sources will reveals the practice of power in disseminating the discourse of halal products using the Foucault’s power-knowledge. In practice, various efforts have been made by the government as the ruler by issuing various regulations as instruments of discourse. There was a discipline of halal products in the form of supervision carried out by the government in which society became the agent for monitoring halal products. Normalization is also carried out by imposing sanctions on products deemed not under regulations. The examination is the last step in the discipline of halal products by the government. This article concludes that government already makes halal-oriented as the new Muslim behaviour. Hence, the decline of religious diversity becomes a new threat as long as the halal issue is held by the only authority.